Bilateral putaminal hemorrhage related to methanol poisoning: a complication of hemodialysis? Case report Hemorragia putaminal bilateral em intoxicação por metanol: uma complicação de hemodiálise? Relato de caso - Miguel Giudicissi Filho; Carlos V. M. Holanda; Nelson A. Nader; Sergio R. P. Gomes; Paulo H. F. Bertolucci (Arquivos de Neuro-Psiquiatria)
A case of acute methanol intoxication is presented, in which bilateral putaminal hemorrhage developed after hemodialysis. Even though the patient was initially comatose and profoundly acidotic, favorable outcome was achieved, with long-term neurologic impairments essentially restricted to mild crural paraparesis, retrograde amnesia, and marked visual deficit. A comparative literature review is evaluated. Um caso de intoxicação aguda por metanol é relatado, no qual o paciente desenvolveu hemorragia putaminal bilateral após hemodiálise. Muito embora o paciente se encontrasse inicialmente comatoso e profundamente acidótico, a recuperação foi favorável, com comprometimento neurológico a longo prazo essencialmente restrito a paraparesia crural discreta, amnésia retrógrada e déficit visual acentuado. Uma revisão comparativa da literatura é avaliada.